CRITICAL INFRASTRUCTURE PROTECTION - STRATEGIC OPPORTUNITIES - Georgi Pavlov; Teodora Gechkova; Tiana Kaleeva (International Journal for Quality Research)
The scope of the current article is regarding the critical infrastructure protection. The goal of the scientific research is to present strategic opportunities for protection of the critical infrastructure's facilities, through outlining and overcoming the critical infrastructure's vulnerabilities. That is achieved based on a conducted survey on the critical infrastructure's vulnerability and outlined strategic mechanisms and activities for improving the critical infrastructure protection, including the introduction of behavioral analysis. The research is accomplished through the application of documentary analysis, comparative analysis and a survey among competent specialists in the researched area.